The Future of Treaty Interpretation in Yahey v British Columbia: Clarification on Cumulative Effects, Common Intentions, and Treaty Infringement - Hamilton, Robert; Ettinger, Nicholas (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2022)
On June 29, 2021, Justice Emily Burke of the Supreme Court of British Columbia ruled that the Province of British Columbia unjustifiably infringed the Treaty 8 rights of Blueberry River First Nation by “permitting the cumulative impacts of industrial development to meaningfully diminish Blueberry’s exercise of its treaty rights.” The decision was a highly anticipated one: Yahey is the first case to explicitly consider whether the cumulative impact of industrial development on a First Nation’s ability to exercise treaty rights in their traditional territory may constitute a treaty infringement. The “piecemeal infringement” of Aboriginal and treaty rights significantly undermines Indigenous peoples’ constitutional rights and legal doctrine has been slow to respond. Several cases are working their way through the courts considering these intractable issues. Yahey provides a well-reasoned and doctrinally sound interpretation of treaty rights that provides a model for what a doctrinal response might look like. This paper outlines the arguments Yahey developed on these issues, sets them within the broader context of the development of treaty interpretation doctrine, and considers how persuasive they ought to be for subsequent courts.